Strategies for agile software development based on technical and environmental complexity factors - Pinciroli, Fernando (2022)
Project management strategies require a perfect understanding of the problem to be faced. For this, the Cynefin framework is a good starting point, offering a way to classify reality according to its complexity. However, there are other aspects that impact and increase the complexity of projects. One of them is the number of triple constraint elements that are fixed; the other, corresponds to project characteristics such as size, criticality, time constraint, etc. In this work we offer a strategy to classify the best tools, techniques and approaches for project management depending on technical and environmental complexity factors.